DIGITAL TRANSFORMATION OF ECONOMIC POTENTIAL MANAGEMENT IN SERVICE ENTERPRISES: A STRATEGIC EFFICIENCY APPROACH (Symposium on Natural and Applied Sciences, 2026)
This article examines the issues of improving the economic potential management system in service enterprises based on digital transformation. In the conditions of the modern economy, the rapid development of digital technologies, in particular artificial intelligence, big data (Big Data) and digital platforms, is becoming an important factor in increasing the efficiency of management in the service sector. During the study, the content of the concept of economic potential was expanded, and its structural elements - material, financial, human capital and intellectual resources - were analyzed based on a systematic approach. The article studies the current state of economic potential management in service enterprises and assesses the impact of digital transformation processes on this system. It also substantiates the possibilities of optimizing management processes, increasing the efficiency of resource use and strengthening competitiveness by developing a digital model of economic potential management. The results of the study serve to increase the efficiency of using digital technologies in making strategic management decisions in service enterprises.
Keywords: Digital transformation, economic potential, service enterprises, strategic management, efficiency, innovation, artificial intelligence, Big Data, competitiveness, resource utilization.